Transformasi Digital dalam Warehouse Management: Eksplorasi Faktor Kunci Keberhasilan Implementasi Teknologi Internet of Things (IoT) pada Sistem Penyimpanan Barang - Steven Andreas Gunawan (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
Digital transformation through Internet of Things (IoT) in warehouse management represents a paradigmatic revolution in contemporary logistics systems. This research comprehensively explores the complexity of IoT implementation, analyzing critical factors influencing digital transformation in storage systems. Utilizing a systematic literature review methodology, the research unveils multidimensional dynamics involving complex interactions between advanced technology, organizational structures, and human resources. Findings indicate that successful IoT implementation requires a holistic approach that transcends mere technological adoption, demanding a fundamental reconstruction of business ecosystems. Key factors include top management support, sustainable infrastructure investment, human resource competency development, and innovation culture creation. The research affirms that digital transformation is not simply a technological project, but a complex strategic journey requiring long-term commitment and sustainable adaptive capabilities. Research implications provide profound insights for academics and practitioners in designing effective digital transformation strategies in warehouse management.